Sustainable financial governance training for civil society organizations (CSOs) in Indonesia - Derry Wanta; Saminem (Privietlab, 2022)
In Indonesia, sustainable finance is defined as the financial services industry's overall support for long-term growth as a result of the alignment of economic, social, and environmental interests. Entities are required to disclose activities related to the economy, social, and environment in which they are profit institutions in the Sustainability Report. Sustainability reports are not required for Civil Society Organizations (CSOs), but CSOs are intimately involved in sustainability activities. The possibility of collaborative activities or funding between profit institutions and CSOs is required. CSOs must be trained in sustainable finance in order to have the same frequency as profit institutions. This is the foundation for holding sustainable finance training activities for CSOs. This training is being offered in collaboration with the Penabulu Foundation and Co Evolve. Sixty people participated in the training activity via Zoom media. Participants in the training included CSOs, workers, students from Indonesian universities, and civil servants. Based on the online sheets received, this training received positive feedback from participants. In general, the participants are welcomed and enthusiastically participated in this training.